Optimization of photovoltaic panel deployment in centralized photovoltaic power plant under multiple factors - Fan, Rongquan; Ming, Ziqiang; Xu, Weiting; Li, Ting; Han, Yuqi; Ma, Ruiguang; Liu, Jichun; Wu, Yiyang (Frontiers in Energy Research, 2023)
Solar energy is one of the main renewable energy sources and has rapidly developed in many countries. However, the photovoltaic (PV) output power will be different under various meteorological and geographical conditions. Therefore, this paper presents an optimization method for the deployment of PV panels in a centralized PV power plant considering multiple factors. Firstly, the whole planning area is divided into a certain amount of sub-areas according to a given area, and fuzzy C-means algorithm is used for terrain clustering according to the geographical characteristics of the sub-areas. Secondly, the correlation analysis between each meteorological factor and PV output power is carried out separately to select the main factors affecting PV output power, and then the expected annual PV output power under the joint action of several main meteorological factors in each terrain is calculated by dual-stage attention mechanism based long short-term memory algorithm. Finally, according to the expected annual PV output of each terrain, considering the constraints including cost, area and so on, the deployment optimization of PV panels is obtained to maximize the annual PV output of the whole PV power plant and minimize the construction cost. The results of case studies show that the proposed methods effectively improve the expected PV output power of the PV power plant and reduce the construction cost.